(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
This article addresses the assessment of data quality in qualitative research. The analysis shows that the use of the qualitative approach in demographic research has a selective approach in terms of topics. It is used to increase the information about a certain problem or to clarify the existing knowledge obtained from the quantitative approach. The criteria for evaluating the quality of qualitative data are in the context of the methodological aspects in the research, but still there is no agreement regarding the framework for evaluating the quality of the data. In perspectives, aspects suggested for assessing data quality are data collection method, sample, selection and training of interviewers, field work and data analysis.